Comparative Analysis of Entry-Level TOEFL Skill Profiles Among Vocational Students: Implications for ESP Curriculum Development - Irfiani Bakri; Alfridha Dwi Putri Putri; Rahmat J; Walangitan Melania Rut (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
English proficiency has become an essential competency for vocational higher education students due to the increasing demand for effective communication in academic, professional, and workplace contexts. Although the Test of English as a Foreign Language (TOEFL) is widely used to assess English proficiency, previous studies have predominantly focused on overall TOEFL achievement, while limited attention has been given to the diagnostic analysis of TOEFL subskills and their implications for English for Specific Purposes (ESP) curriculum development. This study aims to investigate the entry-level TOEFL skill profiles of first-semester vocational students and examine disciplinary differences across Business Management, Business Administration, and Information Technology programs. Employing a quantitative descriptive-comparative design, the study analyzed secondary TOEFL data from 175 first-semester students. The dataset consisted of Listening Comprehension, Structure and Written Expression, Reading Comprehension, and overall TOEFL scores. Descriptive statistics, proficiency classification, and one-way analysis of variance (ANOVA) were used to identify students’ language proficiency profiles and examine differences among academic programs. The findings revealed that Reading Comprehension achieved the highest mean score, followed by Structure and Written Expression, whereas Listening Comprehension emerged as the weakest skill. The majority of students (76.0%) were classified within the low proficiency category. Furthermore, significant differences were found among academic programs, with Information Technology students consistently outperforming Business Management and Business Administration students across all TOEFL components. The findings indicate that vocational students demonstrate distinct language proficiency profiles and disciplinary variations in English competence. This study contributes to the ESP literature by demonstrating the value of TOEFL subskill profiling as a diagnostic needs-analysis tool and by providing empirical evidence for the development of discipline-sensitive and evidence-based ESP curricula in vocational higher education.